Analysis of the Influence of Lempu and Temmappasilaingeng Cultural Values and Services on Customer Loyalty through Satisfaction in Laundry Businesses in Watampone - Herianti Herianti; Sitti Nikmah Marzuki; Ida Farida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the influence of local Bugis cultural values specifically Lempu (honesty and integrity), Temmappasilaingeng (impartial justice), and service quality on customer loyalty through satisfaction in laundry businesses in Watampone. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS 4, involving 120 respondents from three major sub-districts in Bone Regency. The results reveal that Lempu culture does not have a significant effect on customer satisfaction (T = 1.498; p = 0.137) or loyalty (T = 0.542; p = 0.589). Similarly, Temmappasilaingeng does not significantly influence satisfaction (T = 0.746; p = 0.457) or loyalty (T = 1.347; p = 0.180). Service quality, however, significantly affects customer satisfaction (T = 4.984; p = 0.000), but does not directly influence loyalty (T = 0.915; p = 0.362). Meanwhile, customer satisfaction significantly impacts loyalty (T = 2.760; p = 0.007). Mediation analysis also shows that customer satisfaction significantly mediates the relationship between service quality and loyalty (T = 2.437; p = 0.016), but not between Lempu (T = 1.318; p = 0.190) or Temmappasilaingeng (T = 0.702; p = 0.484) and loyalty. In conclusion, customer satisfaction is a key factor in building loyalty, and service quality is the dominant factor driving that satisfaction. Although local culture holds essential moral values, its influence on loyalty needs to be realized in the form of tangible service experiences to be directly felt by customers.